Marketing Mix-7Ps: The Effect on Customer Satisfaction - Basrah Saidani; I Ketut R Sudiarditha (Faculty of Economics, State University of Jakarta., 2019)
Business competition is getting tougher making the marketing mix used as a tool for tactical marketing tools that can be controlled to produce the desired response in the target market. This study aims to determine the magnitude of the influence of marketing mix-7Ps on consumer satisfaction for the elderly in the Special Capital Region of Jakarta. The research method uses a survey with a questionnaire as a data collection tool. Samples were taken using simple random sampling technique produced 70 respondents. Data is processed using multiple regression analysis techniques. The results of the study show that: (1) empirically proven products, prices, distributions, promotions, and processes have a significant influence on customer satisfaction; meaning that the better the product, price, distribution, promotion and process, the more customer satisfaction increases. (2) Empirically proven physical facilities and people do not affect consumer satisfaction; meaning that physical facilities and people do not significantly result in customer satisfaction. Thus the findings of this study prove that physical facilities and people are not the main ones in consuming a product, but the most important thing is the quality of the product itself which can be used according to its function.